Recaudación tributaria y su relación con la ejecución presupuestal en las municipalidades distritales de Belén, Punchana y San Juan Bautista periodo 2021-2022 - Sangama Tamani, Mercedes (2023)
The research aims to know what the municipal tax collection is, considering municipal taxes and excise duties. Which is a problem in most municipalities in the interior of the country. In the same way, it seeks to relate the collection and use of resources both in the area of municipal taxes and in the source of financing directly collected, considering the collection of excise taxes and the functions of solid waste management, citizen security and parks and gardens. For this, an observational and non-experimental investigation was developed, considering the period of 2021 and 2022. The objective was to identify the relationship between the collection and the execution of the resources related to these items, and it was found that the tax collection and the execution budget in the district municipality of Belén do not present a statistical relationship, it was observed that tax collection and budget execution in the district municipality of Punchana during the period present a significant positive relationship, with a Pearson (Rho) correlation coefficient of 0.999, similarly, tax collection and budget execution in the district municipality of San Juan Bautista during the same period present a significant positive relationship, with a Pearson's Rho coefficient of 1,000. In conclusion, it was determined that tax collection and budget execution in the participating district municipalities during the 2021-2022 period present a significant and positive relationship, with a Pearson (Rho) correlation coefficient of 1,000.